Proyecto de actividades recreativas para fomentar la equidad de genero del primer año de bachillerato del colegio técnico Dr. Camilo Gallegos Dominguez de la ciudad de Latacunga del año 2013 -2014 - Umajinga Tipan, Cesar Rodrigo (2015)
The present work was made to contribute with a recreational activities project in order to create relationships between men and women, banned all types of discrimination because the current education practice produces and reproduces knowledge of skills and clearly sexist attitudes that strengthen male and female stereotypes that limit the possibilities of full realization of human beings and help to develop personal attitudes to promote solidarity and respectful practices which will allow to achieve the quality of education which mainly seeks to help with a human development and equitable model ….